THE EFFECTIVENESS OF USING WHATSAPP AS A MEDIA IN ONLINE LEARNING AT GRADE 5 SD N 1 KARANGNONGKO JEPARA - Aida Dwi Fitria; Nur Fajrie; Mohammad Syafruddin Kuryanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Online learning has been carried out at SD N 1 Karangnongko Jepara due to the corona virus outbreak. As a result, learning at elementary schools was transferred online with the help of WhatsApp media. This study aimed to analyze the effectiveness of online learning through WhatsApp media. This study used a phenomenological qualitative research approach. The results showed that online learning using WhatsApp media tended to be less effective. This was influenced by several factors such as the difficulty of the internet signal and the ability of students who were not able to fully masterWhatsApp application. Thus, an evaluation with related parties was required in order to create effective online learning.